2017
DOI: 10.1002/2017jb014510
|View full text |Cite
|
Sign up to set email alerts
|

A Subsolidus Olivine Water Solubility Equation for the Earth's Upper Mantle

Abstract: The pressure and temperature sensitivity of the two most important point hydrous defects in mantle olivine involving Si vacancies (associated to trace amounts of titanium [TiChu‐PD] or exclusively to Si vacancies [Si]) was investigated at subsolidus conditions in a fluid‐saturated natural peridotite from 0.5 to 6 GPa (approximately 20–200 km depth) at 750 to 1050°C. Water contents in olivine were monitored in sandwich experiments with a fertile serpentine layer in the middle and olivine and pyroxene sensor lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 84 publications
(228 reference statements)
6
65
2
1
Order By: Relevance
“…A comparison of FTIR spectra at various pressures ( Figure 6, as well as Bali et al, 2008;Withers et al, 2011) shows that the contribution of Mgsite protons (absorption at 3,150-3,250 cm −1 ) is significant under only relatively low pressure ≤2.5 GPa) and high silica activity conditions (buffered with pyroxene). With increasing pressure, it becomes much less significant and finally negligible at 12 GPa (e.g., Bali et al, 2008;Berry et al, 2005;Lemaire et al, 2004;Padron-Navarta & Hermann, 2017;Smyth et al, 2006). In contrast, with excess MgO, the incorporation of protons in the Mg sites is always negligible.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of FTIR spectra at various pressures ( Figure 6, as well as Bali et al, 2008;Withers et al, 2011) shows that the contribution of Mgsite protons (absorption at 3,150-3,250 cm −1 ) is significant under only relatively low pressure ≤2.5 GPa) and high silica activity conditions (buffered with pyroxene). With increasing pressure, it becomes much less significant and finally negligible at 12 GPa (e.g., Bali et al, 2008;Berry et al, 2005;Lemaire et al, 2004;Padron-Navarta & Hermann, 2017;Smyth et al, 2006). In contrast, with excess MgO, the incorporation of protons in the Mg sites is always negligible.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…To examine this hypothesis, we plot previously reported experimental data of water solubility in forsterite/olivine as a function of pressure in Figure 7 (This study; Bai & Kohlstedt, 1992;Bali et al, 2008;Ferot & Bolfan-Casanova, 2012;Lemaire et al, 2004;Litasov et al, 2007;Matveev et al, 2001;Mosenfelder et al, 2006;Smyth et al, 2006;Withers and Hirschmann, 2008;Withers et al, 2011;Zhao et al, 2004). Because temperature has a significant effect on water solubility (Bali et al, 2008;Ferot & Bolfan-Casanova, 2012), only the literature data at temperatures of 1,200 to 1,300°C are plotted alongside our data in Figure 7 by considering a ± 50°C temperature uncertainty in large-volume high-pressure experiments even though data exit over a wider temperature range (e.g., Kohlstedt et al, 1996;Padron-Navarta & Hermann, 2017;Withers & Hirschmann, 2008). Additionally, because different infrared calibrations (Bell et al, 2003;Paterson, 1982;Withers et al, 2012) were adopted in these studies, all data are adjusted to the Withers et al (2012) calibration by simply using…”
Section: Pressure Dependence Of Water Solubility In Forsterite/olivinementioning
confidence: 99%
“…The long-term retention of noble gases and halogens in subducting slabs is also made more likely by the increasing solubility of H 2 O in nominally anhydrous minerals, including olivine polymorphs, with depth (Kohlstedt et al, 1996). A recent experimental study has shown that in addition to fluid inclusions (Fig 2f; Scambelluri et al, 2015), about 50 ppm H 2 O is incorporated into the lattice of olivine after the breakdown of chlorite (Padrón-Navarta and Hermann, 2017). An even greater amount of H 2 O would be expected in the lattice of olivine formed at greater depths by the eventual breakdown of Phase A on cold slab geotherms (cf.…”
Section: Volatiles Returned To the Mantlementioning
confidence: 99%
“…Many experimental and theoretical studies have been reported exploring the hydrogen substitution mechanisms: (1) Mg 2+ /Fe 2+ vacancies [1,2,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26], which is the most common substitution in many hydrous silicate minerals; (2) Si 4+ vacancies [27][28][29][30][31][32][33][34][35]; (3) combinations of Mg 2+ , Si 4+ , Ti 4+ , with M 3+ vacancies [28,29,31,[36][37][38][39][40][41][42][43]. In addition, another hydration mechanism with F-substitution is also proposed in both Fe-free and Fe-bearing olivine [44].…”
Section: Introductionmentioning
confidence: 99%